Composite lithium metal negative electrode sheet and preparation method and application thereof
Patent Information
- Application Number
- CN202510500110.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请的目的之一在于提供一种复合锂金属负极片的制备方法,以解决现有技术中的制备方法工艺复杂、增加锂金属负极片生产难度的问题;目的之二在于提供一种复合锂金属负极片,以解决现有技术中锂枝晶在负极不可控的生长会影响锂金属负极片稳定性和安全性,进而影响电池循环性能的问题;目的之三在于提供一种固态电池;目的之四在于提供一种用电设备
[0036](1)本申请提供的复合锂金属负极片的制备方法,包括如下步骤:S1,准备含锂金属片,将其置于电解液中进行阳极氧化处理;S2,将经过阳极氧化处理的含锂金属片在非活泼气体氛围下进行退火处理;S3,将固态电解质和粘结剂进行匀浆,得到浆料,涂覆至经过退火处理后含锂金属片的一侧表面,烘干,辊压,得到所述复合锂金属负极片。根据上述技术手段,本申请创新性的提出直接在含锂金属片表面进行阳极氧化处理来获得更微小的纳米尺寸多孔结构,使得锂离子的沉积位点更多更均匀,降低了表面局部区域的电流密度,可促进Li的均匀沉积,有效抑制锂枝晶的生长,降低电池内短路风险,增强锂金属负极的循环稳定性和安全性能;经过阳极氧化和退火处理,能够在多孔结构的表面原位形成一层无机钝化层,相当于提前在含锂金属片表面预处理制备出一层富含无机物的SEI膜,增强含锂金属片表面的空气稳定性,减轻负极表面/电解质表面的化学不稳定性;将固态电解质层通过涂覆方式与含锂金属片进行组合,不会破环固态电解质中颗粒的完整性、颗粒与颗粒之间保持良好电接触,对固态电解质的形态无要求,在工艺上更具可实施性;并且,含锂金属片表面均匀的纳米多孔结构还能够提高与固态电解质层之间的粘结力,降低固态电解质层与含锂金属片间的界面电阻和机械失效。另外,上述制备方法工艺简单,操作方便,便于大规模工业化生产。
Smart Images

Figure CN123017896A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of solid-state battery technology, specifically relating to a composite lithium metal anode sheet, its preparation method, and its application. Background Technology
[0002] With the rapid development of the new energy industry, batteries are pursuing higher energy density and better safety performance. In response to market demands, next-generation battery technology is moving towards solid-state batteries, and lithium metal anodes are considered a key material for this next generation. Lithium metal anodes have extremely high specific capacity in lithium-ion secondary batteries, and compared to ordinary anodes, they reduce the weight of the anode side, significantly improving battery energy density. However, the main reason limiting the widespread application of lithium metal anodes is the uncontrollable growth of lithium dendrites during charging and discharging, which poses a significant challenge to the stability and safety of lithium metal anodes.
[0003] Currently, the main methods for suppressing lithium dendrites are to prepare a high-strength protective layer on the surface of the lithium foil, such as a lithium fluoride or aluminum oxide layer, to prevent lithium dendrites from piercing through. Another method is to improve the problem of uneven lithium ion deposition by preparing porous structures. However, the existing technology for preparing lithium metal anodes is complex and involves many steps, which increases the difficulty of large-scale production of lithium metal anodes. In addition, the multilayer structure of lithium metal anodes will affect the transport of lithium ions to a certain extent, while increasing the weight of the anode side and reducing the energy density. Summary of the Invention
[0004] One objective of this application is to provide a method for preparing a composite lithium metal anode sheet, so as to solve the problem that the preparation method in the prior art is complex and increases the difficulty of producing lithium metal anode sheets; another objective is to provide a composite lithium metal anode sheet, so as to solve the problem that the uncontrollable growth of lithium dendrites on the anode in the prior art will affect the stability and safety of the lithium metal anode sheet, and thus affect the cycle performance of the battery; a third objective is to provide a solid-state battery; and a fourth objective is to provide an electrical device.
[0005] To achieve the above objectives, the technical solution adopted in this application is as follows:
[0006] According to one aspect of this application, a method for preparing a composite lithium metal anode sheet is provided, comprising the following steps:
[0007] S1. Prepare lithium-containing metal sheets and place them in an electrolyte for anodic oxidation treatment.
[0008] S2, the lithium-containing metal sheet that has undergone anodizing is annealed in a non-reactive gas atmosphere;
[0009] S3, the solid electrolyte and binder are homogenized to obtain a slurry, which is then coated onto one side of the lithium metal sheet after annealing, dried, and rolled to obtain the composite lithium metal anode sheet.
[0010] Based on the aforementioned technical means, this application innovatively proposes to directly perform anodizing treatment on the surface of lithium-containing metal sheets to obtain smaller nano-sized porous structures. This results in more and more uniform lithium-ion deposition sites, reduces the current density in local areas of the surface, promotes uniform Li deposition, effectively inhibits the growth of lithium dendrites, reduces the risk of short circuits in the battery, and enhances the cycle stability and safety performance of the lithium metal anode. After anodizing and annealing, an inorganic passivation layer can be formed in situ on the surface of the porous structure, which is equivalent to pre-treating the surface of the lithium-containing metal sheet to prepare an inorganic-rich SEI film, enhancing the air stability of the lithium-containing metal sheet surface and reducing the chemical instability of the anode / electrolyte surface. Combining the solid electrolyte layer with the lithium-containing metal sheet through coating does not disrupt the integrity of the particles in the solid electrolyte, maintains good electrical contact between particles, has no requirements on the morphology of the solid electrolyte, and is more feasible in terms of process. Furthermore, the uniform nanoporous structure on the surface of the lithium-containing metal sheet can also improve the adhesion between the solid electrolyte layer and the solid electrolyte layer, and reduce the interfacial resistance and mechanical failure between the solid electrolyte layer and the lithium-containing metal sheet. In addition, the above preparation method is simple, easy to operate, and convenient for large-scale industrial production.
[0011] In some optional embodiments, in S1, the parameters of the anodizing treatment include: an electrolysis temperature of 20–40°C, an electrolysis time of 2–10 min, and a voltage range of 0.005–3 V.
[0012] In this application, by adjusting the parameters of the anodic oxidation process, the size, uniformity, and thickness of the passivation layer of the nanoporous structure can be controlled.
[0013] And / or, the lithium-containing metal sheet includes at least one of pure lithium metal sheet or lithium-containing alloy; optionally, the lithium-containing alloy includes at least one of Li-B alloy, Li-Al alloy, Li-Cu alloy, Li-Zn alloy, Li-Sn alloy, and Li-In alloy.
[0014] In some optional embodiments, in S1, the anodic oxidation step uses a lithium-containing metal sheet as the anode and a platinum electrode as the cathode.
[0015] And / or, the electrolyte includes a lithium salt with a concentration of 0.5 mol / L to 5 mol / L.
[0016] This application enables the control of the size of nanoporous structures by limiting the concentration of lithium salt in the electrolyte, resulting in a more uniform pore structure distribution. Too low or too high a lithium salt concentration may lead to larger pore sizes and uneven pore distribution.
[0017] In some optional embodiments, in S2, the annealing treatment is carried out at a temperature of 100–700°C for a time of 0.5–4 h and a heating rate of 5–10°C / min.
[0018] And / or, the inert gas includes at least one of argon and nitrogen.
[0019] This application, by controlling the operating parameters and atmosphere of the annealing step, can partially decompose the inorganic materials of different compositions formed in the anodizing step, transforming them into a more stable inorganic passivation layer, while simultaneously avoiding the impact of annealing on the performance of lithium-containing metal sheets or solid electrolytes. For example, lithium carbonate (Li2CO3) decomposes into lithium oxide (Li2O) and carbon dioxide (CO2) at high temperatures, and lithium hydroxide (LiOH) decomposes into lithium oxide (Li2O) and water (HO2) at high temperatures.
[0020] And / or, in S3, the drying temperature is 60-80°C.
[0021] According to another aspect of this application, a composite lithium metal anode sheet is provided, which is prepared by the above-described preparation method.
[0022] In some alternative embodiments, the composite lithium metal anode sheet comprises,
[0023] A lithium-containing metal sheet has a first surface and a second surface opposite each other in its own thickness direction, and at least one surface has a nanoporous structure;
[0024] The surface components of the nanoporous structure include at least one of lithium oxide, lithium hydroxide, lithium carbonate, and lithium fluoride.
[0025] A solid electrolyte layer is located on one side surface of the lithium-containing metal sheet and fills the nanoporous structure.
[0026] Based on the above technical means, this application forms a passivation layer in situ between the lithium-containing metal sheet and the solid electrolyte layer of the composite lithium metal anode sheet. This passivation layer can serve as an SEI film to enhance the air stability of the lithium metal sheet surface and reduce the chemical instability of the lithium metal sheet surface / electrolyte surface. The surface of the lithium-containing metal sheet is provided with a smaller nanoscale pore structure, which makes the lithium ion deposition sites more numerous and uniform, effectively suppressing the growth of lithium dendrites and improving the cycle performance of the battery.
[0027] In some optional embodiments, the average pore size of the nanoporous structure is 20–80 nm. In this application, the average pore size of the nanoporous structure can be tested using methods and equipment known in the art, for example, by characterizing the surface and cross-section of a lithium-containing metal sheet using a scanning electron microscope.
[0028] And / or, the thickness of the lithium-containing metal sheet is 10–30 μm. In this application, limiting the thickness of the lithium-containing metal sheet to the above range can significantly improve the energy density of the lithium-ion battery while taking into account the mechanical properties of the electrode. Theoretically, the thinner the metal sheet, the lighter the weight and the higher the energy density of the battery. However, the thinner the lithium-containing metal sheet, the worse its self-support, and it is prone to damage during the preparation of lithium-ion batteries.
[0029] And / or, the thickness of the solid electrolyte layer is 10-50 μm. In this application, the thickness of the solid electrolyte layer is limited to the above range. In solid-state batteries, the solid electrolyte serves as both a separator and an electrolyte. If the thickness is less than 10 μm, it cannot effectively prevent the penetration of trace lithium dendrites or other foreign matter, which may lead to internal short circuits. If the thickness is greater than 50 μm, it will result in longer ion and electron transport paths and poorer charge and discharge performance. At the same time, the thickness of the solid electrolyte layer is also closely related to the energy density; the thicker the layer, the lower the energy density.
[0030] In some alternative embodiments, the solid electrolyte layer comprises 93% to 97% solid electrolyte and 3% to 7% binder by weight.
[0031] In some optional embodiments, the solid electrolyte includes at least one of sulfide solid electrolyte, halide solid electrolyte, oxide electrolyte, and polymer electrolyte. In this application, a solid electrolyte material with high stability to lithium metal is preferred, which can reduce side reactions at the interface between the solid electrolyte and the lithium-containing metal sheet and enhance the interfacial stability between them.
[0032] According to another aspect of this application, a lithium-ion solid-state battery is also provided, comprising a composite lithium metal anode sheet prepared by the above-described preparation method.
[0033] According to another aspect of this application, an electrical device is also provided, including the aforementioned lithium-ion solid-state battery.
[0034] In this application, the lithium-ion solid-state battery and the electrical device described herein have the same advantages over the prior art as the aforementioned composite lithium metal anode sheet, and will not be repeated here.
[0035] The beneficial effects of this application are:
[0036] (1) The method for preparing the composite lithium metal anode sheet provided in this application includes the following steps: S1, preparing a lithium metal sheet and placing it in an electrolyte for anodic oxidation treatment; S2, annealing the anodic oxidized lithium metal sheet in a non-reactive gas atmosphere; S3, homogenizing the solid electrolyte and binder to obtain a slurry, coating it onto one side surface of the annealed lithium metal sheet, drying it, and rolling it to obtain the composite lithium metal anode sheet. Based on the aforementioned technical means, this application innovatively proposes to directly perform anodizing treatment on the surface of lithium-containing metal sheets to obtain smaller nano-sized porous structures. This results in more and more uniform lithium-ion deposition sites, reduces the current density in local areas of the surface, promotes uniform Li deposition, effectively inhibits the growth of lithium dendrites, reduces the risk of short circuits in the battery, and enhances the cycle stability and safety performance of the lithium metal anode. After anodizing and annealing, an inorganic passivation layer can be formed in situ on the surface of the porous structure, which is equivalent to pre-treating the surface of the lithium-containing metal sheet to prepare an inorganic-rich SEI film, enhancing the air stability of the lithium-containing metal sheet surface and reducing the chemical instability of the anode / electrolyte surface. Combining the solid electrolyte layer with the lithium-containing metal sheet through coating does not disrupt the integrity of the particles in the solid electrolyte, maintains good electrical contact between particles, has no requirements on the morphology of the solid electrolyte, and is more feasible in terms of process. Furthermore, the uniform nanoporous structure on the surface of the lithium-containing metal sheet can also improve the adhesion between the solid electrolyte layer and the solid electrolyte layer, and reduce the interfacial resistance and mechanical failure between the solid electrolyte layer and the lithium-containing metal sheet. In addition, the above preparation method is simple, easy to operate, and convenient for large-scale industrial production.
[0037] (2) In this application, by adjusting the parameters of the anodic oxidation process, the size, uniformity and thickness of the nanoporous structure and the passivation layer can be controlled.
[0038] (3) By limiting the concentration of lithium salt in the electrolyte, this application can control the size of the nanoporous structure, making the pore structure distribution more uniform. Too small or too large a concentration of lithium salt may lead to larger pore size and uneven pore distribution.
[0039] (4) By controlling the operating parameters and atmosphere of the annealing step, this application can decompose the inorganic materials with different compositions formed in the anodic oxidation step into a more stable inorganic passivation layer, while avoiding the impact of annealing on the performance of lithium metal sheets or solid electrolytes.
[0040] (5) The composite lithium metal anode sheet provided in this application is prepared by the above-described preparation method. According to the above technical means, this application forms a passivation layer in situ between the lithium-containing metal sheet and the solid electrolyte layer of the composite lithium metal anode sheet. This passivation layer can serve as an SEI film to enhance the air stability of the lithium metal sheet surface and reduce the chemical instability of the lithium metal sheet surface / electrolyte surface. The surface of the lithium-containing metal sheet has a smaller nanoscale pore structure, which makes the lithium ion deposition sites more numerous and uniform, effectively suppressing the growth of lithium dendrites and improving the cycle performance of the battery.
[0041] (6) In this application, by limiting the thickness of the lithium metal sheet, the energy density of the lithium-ion battery can be greatly improved, while taking into account the mechanical properties of the electrode. Theoretically, the thinner the lithium metal sheet, the lighter the weight and the higher the energy density of the battery. However, the thinner the lithium metal sheet, the worse its self-support, and it is easy to be damaged during the preparation of lithium-ion batteries.
[0042] (7) In this application, by limiting the thickness of the solid electrolyte layer, it is possible to achieve a balance between safety performance, energy density, and ion and electron transport performance. In solid-state batteries, the solid electrolyte must simultaneously act as a separator and electrolyte. If the thickness is too small, it may cause the penetration of trace lithium dendrites or other foreign objects, resulting in an internal short circuit. If the thickness is too large, it will cause the transport path of ions and electrons to become longer, resulting in poorer charge and discharge performance. At the same time, the thickness of the solid electrolyte layer is also closely related to the energy density. The thicker the layer, the lower the energy density.
[0043] (8) In this application, a solid electrolyte material with high stability to lithium metal is preferred, which can reduce the side reaction at the interface between the solid electrolyte and the lithium metal sheet and enhance the interface stability between the two.
[0044] (9) In this application, the lithium-ion solid-state battery and the electrical device have the same advantages as the above-mentioned composite lithium metal anode sheet over the prior art, and will not be repeated here.
[0045] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0046] Figure 1 This is a schematic diagram of the structure of the composite lithium metal anode sheet provided in this application;
[0047] Figure 2 This is a schematic diagram of the composite lithium metal anode sheet provided in Embodiment 1 of this application;
[0048] Figure 3 This is a top view of the coating of the adhesive layer in Embodiment 1 of this application;
[0049] Figure 4 This is a process flow diagram of the preparation of the composite lithium metal anode sheet in the embodiments of this application;
[0050] Among them, 1. Lithium-containing metal sheet; 2. Solid electrolyte layer; 3. Nanoporous structure; 4. Electrode; 5. Adhesive layer. Detailed Implementation
[0051] The following embodiments are provided to better understand this application and are not limited to the preferred embodiments described herein. They do not constitute a limitation on the content and scope of protection of this application. Any product that is the same as or similar to this application, derived by anyone under the guidance of this application or by combining features of this application with other prior art, falls within the scope of protection of this application.
[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having” and any variations thereof in the text of this application are intended to cover non-exclusive inclusion.
[0053] In the description of the embodiments of this application, the technical terms "first", "second", etc. are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0054] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0055] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers from a to b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed herein; "0-5" is merely a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥ 2, it is equivalent to disclosing that the parameter can be, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0056] In the description of the embodiments of this application, the term "and / or" is merely a description of the relationship between related objects, indicating that there can be three relationships. For example, A and / or B can represent three situations: A exists alone, A and B exist simultaneously, and B exists alone.
[0057] In the description of the embodiments of this application, the term "at least one" refers to one or more (including two).
[0058] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0059] It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of this application. The drawings only show the components related to this application and are not drawn according to the actual number, shape and size of the components in the actual implementation. In the actual implementation, the form, quantity and proportion of each component can be arbitrarily changed, and the layout of the components may also be more complex.
[0060] As described in the background section, the existing methods for preparing lithium metal anode sheets have problems such as complex processes, which increase the difficulty of producing lithium metal anode sheets; and the improvement effect on lithium dendrites needs to be further improved, as dendrite growth on the anode still exists, which affects the stability and safety of lithium metal anode sheets, and thus affects the battery cycle performance.
[0061] Based on this, this application provides a method for preparing a composite lithium metal anode sheet, comprising the following steps:
[0062] S1. Prepare lithium-containing metal sheets and place them in an electrolyte for anodic oxidation treatment.
[0063] S2, the lithium-containing metal sheet that has undergone anodizing is annealed in a non-reactive gas atmosphere;
[0064] S3, the solid electrolyte and binder are homogenized to obtain a slurry, which is then coated onto one side of the lithium metal sheet after annealing, dried, and rolled to obtain the composite lithium metal anode sheet.
[0065] Based on the aforementioned technical means, this application innovatively proposes to directly perform anodizing treatment on the surface of lithium-containing metal sheets to obtain smaller nano-sized porous structures. This results in more and more uniform lithium-ion deposition sites, reduces the current density in local areas of the surface, promotes uniform Li deposition, effectively inhibits the growth of lithium dendrites, reduces the risk of short circuits in the battery, and enhances the cycle stability and safety performance of the lithium metal anode. After anodizing and annealing, an inorganic passivation layer can be formed in situ on the surface of the porous structure, which is equivalent to pre-treating the surface of the lithium-containing metal sheet to prepare an inorganic-rich SEI film, enhancing the air stability of the lithium-containing metal sheet surface and reducing the chemical instability of the anode / electrolyte surface. Combining the solid electrolyte layer with the lithium-containing metal sheet through coating does not disrupt the integrity of the particles in the solid electrolyte, maintains good electrical contact between particles, has no requirements on the morphology of the solid electrolyte, and is more feasible in terms of process. Furthermore, the uniform nanoporous structure on the surface of the lithium-containing metal sheet can also improve the adhesion between the solid electrolyte layer and the solid electrolyte layer, and reduce the interfacial resistance and mechanical failure between the solid electrolyte layer and the lithium-containing metal sheet. In addition, the above preparation method is simple, easy to operate, and convenient for large-scale industrial production.
[0066] It should be noted that when only a nanoscale porous structure needs to be formed on one side of the lithium metal sheet, protective treatments can be applied to other surfaces, such as by applying adhesive tape.
[0067] In some optional embodiments, in S1, the parameters of the anodizing treatment include: an electrolysis temperature of 20–40°C, an electrolysis time of 2–10 min, and a voltage range of 0.005–3V. For example, the electrolysis temperature can be 20°C, 25°C, 30°C, 35°C, 40°C, or any range thereof; the electrolysis time can be 2 min, 4 min, 5 min, 6 min, 8 min, 10 min, or any range thereof; and the voltage can be 0.005V, 0.1V, 0.5V, 1V, 1.3V, 1.8V, 2V, 2.5V, 3V, or any range thereof.
[0068] In this application, by adjusting the parameters of the anodic oxidation process, the size, uniformity, and thickness of the passivation layer of the nanoporous structure can be controlled.
[0069] And / or, the lithium-containing metal sheet includes at least one of pure lithium metal sheet or lithium-containing alloy; optionally, the lithium-containing alloy includes at least one of Li-B alloy, Li-Al alloy, Li-Cu alloy, Li-Zn alloy, Li-Sn alloy, and Li-In alloy.
[0070] In some optional embodiments, in S1, the anodic oxidation step uses a lithium-containing metal sheet as the anode and a platinum electrode as the cathode.
[0071] And / or, the electrolyte includes a lithium salt with a concentration of 0.5 mol / L to 5 mol / L; as an example, the concentration of lithium salt in the electrolyte can be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, or within any range of the above values. This application, by limiting the concentration of lithium salt in the electrolyte, can achieve control over the size of the nanoporous structure, resulting in a more uniform pore structure distribution. Too low or too high a lithium salt concentration may lead to excessively large pore sizes and uneven pore distribution.
[0072] In this application, the lithium salt includes, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium carbonate, lithium perchlorate (LiCLO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborohydride (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalateborate)borate (LiBOB), lithium difluorooxalateborate (LiODFB), and lithium hydroxide (LiOH).
[0073] In some alternative embodiments, the solvent in the electrolyte includes, but is not limited to, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), organic solvents, and water.
[0074] In this application, by adjusting the electrolyte of different lithium salts during the anodizing process, passivation layers with different compositions can be prepared on the porous surface of lithium metal sheets. For example, anodizing in lithium hexafluorophosphate (LiPF6) electrolyte can prepare lithium fluoride (LiF) on the surface of lithium metal sheets, and anodizing in lithium carbonate (Li2CO3) electrolyte can prepare lithium carbonate on the surface of lithium metal sheets. Different lithium-containing inorganic substances can be obtained by using different lithium salts. It is preferred to use electrolytes containing F and Cl for anodizing treatment, resulting in passivation layers with a higher content of inorganic substances.
[0075] In some optional embodiments, in S2, the annealing temperature is 100–700°C, the time is 0.5–4 h, and the heating rate is 5–10°C / min. For example, the annealing temperature can be 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, or any range thereof; the annealing time can be 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, or any range thereof; and the heating rate can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or any range thereof.
[0076] And / or, the inert gas includes at least one of argon and nitrogen.
[0077] This application, by controlling the operating parameters and atmosphere of the annealing step, can partially decompose the inorganic materials of different compositions formed in the anodizing step, transforming them into a more stable inorganic passivation layer, while simultaneously avoiding the impact of annealing on the performance of lithium-containing metal sheets or solid electrolytes. For example, lithium carbonate (Li2CO3) decomposes into lithium oxide (Li2O) and carbon dioxide (CO2) at high temperatures, and lithium hydroxide (LiOH) decomposes into lithium oxide (Li2O) and water (HO2) at high temperatures.
[0078] And / or, in S3, the drying temperature is 60–80°C. As an example, the drying temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, or within any range of the above values.
[0079] In some alternative embodiments, the step of preparing the tab is also included. The tab is prepared in a conventional manner in the art, and can be prepared by bonding or welding. When bonding is used, a layer of slurry can be applied to the tab area, and then the tab is covered over the slurry area to bond the tab to the tab area.
[0080] According to another aspect of this application, a composite lithium metal anode sheet is provided, which is prepared by the above-described preparation method.
[0081] In some alternative embodiments, the structural schematic diagram of the composite lithium metal anode sheet is as follows: Figure 1 As shown, including,
[0082] A lithium-containing metal sheet 1 has a first surface and a second surface opposite to each other in its own thickness direction, and at least one surface has a nanoporous structure 3;
[0083] The surface composition of the nanoporous structure 3 includes at least one of lithium oxide, lithium hydroxide, lithium carbonate, and lithium fluoride.
[0084] A solid electrolyte layer 2 is located on one side surface of the lithium-containing metal sheet 1 and fills the nanoporous structure 3.
[0085] Based on the above technical means, this application forms a passivation layer (not shown in the figure) in situ between the lithium-containing metal sheet and the solid electrolyte layer of the composite lithium metal anode sheet. This passivation layer can serve as an SEI film to enhance the air stability of the lithium metal sheet surface and reduce the chemical instability of the lithium metal sheet surface / electrolyte surface. The surface of the lithium metal sheet is provided with a smaller nanoscale pore structure, which makes the lithium ion deposition sites more numerous and uniform, effectively suppressing the growth of lithium dendrites and improving the cycle performance of the battery.
[0086] In some optional embodiments, the average pore size of the nanoporous structure is 20–80 nm; as an example, the average pore size of the nanoporous structure can be 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, or within any range of the above values. In this application, the average pore size of the nanoporous structure can be tested using methods and equipment known in the art, for example, characterizing the surface and cross-section of a lithium-containing metal sheet using a scanning electron microscope.
[0087] And / or, the thickness of the lithium-containing metal sheet is 10 to 30 μm; as an example, the thickness of the lithium-containing metal sheet can be 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, or within any of the above values.
[0088] In this application, limiting the thickness of the lithium-containing metal sheet to the above-mentioned range can significantly improve the energy density of the lithium-ion battery while taking into account the mechanical properties of the electrode. Theoretically, the thinner the lithium-containing metal sheet, the lighter the weight and the higher the energy density of the battery. However, the thinner the lithium-containing metal sheet, the worse its self-support, and it is prone to damage during the preparation of lithium-ion batteries.
[0089] And / or, the thickness of the solid electrolyte layer is 10-50 μm. As an example, the thickness of the solid electrolyte layer can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or within any range of the above values.
[0090] In this application, the thickness of the solid electrolyte layer is limited to the above-mentioned range. In solid-state batteries, the solid electrolyte serves as both a separator and an electrolyte. If the thickness is less than 10 μm, it cannot effectively prevent the penetration of trace lithium dendrites or other foreign matter, which may lead to internal short circuits. If the thickness is greater than 50 μm, it will result in longer ion and electron transport paths and poorer charge and discharge performance. At the same time, the thickness of the solid electrolyte layer is also closely related to the energy density. The thicker the layer, the lower the energy density.
[0091] In some alternative embodiments, the solid electrolyte layer comprises 93% to 97% solid electrolyte and 3% to 7% binder by weight.
[0092] In some optional embodiments, the solid electrolyte includes at least one of sulfide solid electrolytes, halide solid electrolytes, oxide electrolytes, and polymer electrolytes. For example, the sulfide solid electrolytes include, but are not limited to, Li₂S-P₂S₅ type, LISICON type, and sulfide-germanium ore type; the chemical formula of the halide solid electrolyte can be Li₂MX₄, where M = Mg, Ti, V, Cr, Mn, Fe, Co, Ni, Cd, etc., and X = Cl, Br, or I; the oxide electrolyte can be garnet-type lithium lanthanum zirconium oxide (LLZO), perovskite-type lithium lanthanum titanium oxide (LLTO), fast ion conductor type lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), etc.; the polymer electrolyte can be polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), etc.
[0093] In this application, a solid electrolyte material with high stability to lithium metal is preferred, which can reduce the side reactions at the interface between the solid electrolyte and the lithium metal sheet and enhance the interfacial stability between the two.
[0094] In some alternative embodiments, the adhesive includes, but is not limited to, at least one of polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), polyethylene oxide (PEO), polyacrylonitrile (PAN), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), alginate, etc.
[0095] According to another aspect of this application, a lithium-ion solid-state battery is also provided, comprising a composite lithium metal anode sheet prepared by the above-described preparation method.
[0096] According to another aspect of this application, an electrical device is also provided, including the aforementioned lithium-ion solid-state battery.
[0097] Those skilled in the art will understand that the lithium-ion solid-state battery provided in this application includes, in addition to the aforementioned composite lithium metal negative electrode, also a positive electrode, a casing, and other structural components. During the charging and discharging process, lithium ions repeatedly insert and extract between the positive and negative electrode.
[0098] As an example, the positive electrode sheet includes a positive current collector and a positive active material layer. The positive current collector has two opposing surfaces in its own thickness direction, and the positive active material layer is disposed on either or both of the opposing surfaces of the negative current collector. The materials, composition, and manufacturing methods of the positive electrode sheet used in the lithium-ion battery of this application may include any techniques disclosed in the prior art.
[0099] This application does not specify a particular method for preparing lithium-ion solid-state batteries; lithium-ion solid-state batteries can be prepared using conventional methods in the field.
[0100] It is understood that in the electrical equipment provided in this application, the lithium-ion solid-state battery can be used as a power source for the electrical equipment, or as an energy storage unit for the electrical equipment. The electrical equipment may be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0101] The lithium-ion solid-state battery and electrical equipment described above have the same advantages over the prior art as the composite lithium metal anode sheet, and will not be repeated here.
[0102] The present application will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present application in any way.
[0103] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0104] Example 1
[0105] This embodiment provides a composite lithium metal anode sheet, the structural schematic of which is shown below. Figure 2 and Figure 3 As shown, it includes: a lithium-containing metal sheet 1, having a first surface and a second surface opposite each other in its own thickness direction, and at least one surface having a nanoporous structure 3;
[0106] The surface composition of the nanoporous structure 3 includes at least one of lithium oxide, lithium hydroxide, lithium carbonate, and lithium fluoride.
[0107] A solid electrolyte layer 2 is located on one side surface of the lithium-containing metal sheet 1 and fills the nanoporous structure 3. The lithium-containing metal sheet 1 includes a coating area and a tab area, and the solid electrolyte layer is located in the coating area.
[0108] The tab 4 is disposed in the tab area of the lithium metal sheet 1 through the adhesive layer 5.
[0109] The fabrication process diagram of the composite lithium metal anode sheet is as follows: Figure 4 As shown, the specific steps are as follows:
[0110] (1) First, the surface of the lithium-containing metal sheet with a thickness of 20μm is cleaned to remove residual oil and impurities on the sample surface, and then dried for later use.
[0111] (2) The surface of the lithium metal sheet (pure lithium metal sheet in this embodiment) is subjected to anodic oxidation treatment. The lithium metal sheet is anodic oxidized in a two-electrode electrolytic cell with a platinum sheet as the cathode. The two electrodes are immersed in the electrolyte. The lithium salt in the electrolyte is lithium hexafluorophosphate with a concentration of 2 mol / L. The solvent is dimethyl carbonate (DMC). The electrolyte is in a constant temperature device with a temperature of 20°C, a voltage of 3V, and an oxidation time of 10 min to obtain the oxidized lithium metal sheet. After drying, it is ready for use.
[0112] (3) The lithium metal sheet after anodizing was annealed in an argon atmosphere, with the heating rate controlled at 6℃ / min, the temperature at 150℃ and the holding time at 2h. According to the test, the average pore size of the passivation layer surface pore structure in this embodiment is 50nm.
[0113] (4) Sodium carboxymethyl cellulose (CMC), conductive carbon black (SP), and carbon nanotubes (CNT) are mixed evenly in a ratio of 5:90:5 to obtain slurry A. The solvent is water and the solid content is 80%. Slurry A is coated on the surface of the lithium metal sheet tab area, and the coating thickness is controlled to be 5μm. Copper tabs are then placed on the sheet.
[0114] (5) Mix Li6PS5Cl solid electrolyte powder and sodium carboxymethyl cellulose (CMC) at a ratio of 96:4 to obtain slurry B. The solvent is tetrahydrofuran (THF) and ethanol, and the solid content is 75%. Coat the slurry B on the coating area of the lithium metal sheet, and control the coating thickness to 20 μm. After the electrode is dried at 80°C, roll the electrode to obtain a composite lithium metal negative electrode.
[0115] Example 2
[0116] This embodiment provides a composite lithium metal anode sheet. Compared with Embodiment 1, the difference is that the thickness of the lithium metal sheet in step (1) is 15 μm; the mass ratio of CMC, SP, and CNT in slurry A is 3:92:5; and the solid electrolyte in slurry B is Li. 5.5 PS 4.5 Cl 1.5 Li in slurry B 5.5 PS 4.5 Cl 1.5 The mass ratio of slurry B to CMC is 95:5, and the coating thickness of slurry B is controlled to be 15μm.
[0117] Example 3
[0118] This embodiment provides a composite lithium metal anode sheet. Compared with Embodiment 1, the difference is that the thickness of the lithium metal sheet in step (1) is 30 μm; the slurry A does not include CNTs, and the mass ratio of CMC to SP is 5:95; the solid electrolyte in the slurry B is Li7PS3Cl. 11 Li7PS3Cl in slurry B 11 The mass ratio of slurry B to CMC is 97:3, and the coating thickness of slurry B is controlled to be 30μm.
[0119] Example 4
[0120] This embodiment provides a composite lithium metal anode sheet. Compared with Embodiment 1, the difference lies in the anodic oxidation operating conditions. Specifically, the lithium salt in the electrolyte is lithium difluorooxalate borate with a concentration of 1 mol / L, the solvent is ethylene carbonate, and the electrolyte is placed in a constant temperature device with a controlled temperature of 20°C, a voltage of 0.005V, and an oxidation time of 2 minutes. Testing showed that the average pore size of the nanoporous structure on the surface of the lithium metal sheet in this embodiment is 25 nm.
[0121] Example 5
[0122] This embodiment provides a composite lithium metal anode sheet. Compared with Embodiment 1, the difference lies in the anodic oxidation operating conditions. Specifically, the lithium salt in the electrolyte is lithium carbonate with a concentration of 5 mol / L, the solvent is dimethyl carbonate, and the electrolyte is placed in a constant temperature device, controlling the temperature at 40°C, the voltage at 3V, and the oxidation time at 10 min. Testing showed that the average pore size of the nanoporous structure on the surface of the lithium metal sheet in this embodiment is 75 nm.
[0123] Example 6
[0124] This embodiment provides a composite lithium metal anode sheet. Compared with Embodiment 1, the difference lies in the different operating conditions of the annealing treatment. Specifically, the heating rate is controlled at 10℃ / min, the temperature at 600℃, and the holding time at 4h.
[0125] Example 7
[0126] This embodiment provides a composite lithium metal anode sheet. Compared with Embodiment 1, the difference lies in the different operating conditions of the annealing treatment. Specifically, the heating rate is controlled at 5℃ / min, the temperature at 100℃, and the holding time at 0.5h.
[0127] Example 8
[0128] This embodiment provides a composite lithium metal anode sheet. The difference from Embodiment 1 is that the composition of the solid electrolyte in slurry B is different. In this embodiment, the solid electrolyte is Li2MnCl4.
[0129] Example 9
[0130] This embodiment provides a composite lithium metal anode sheet. The difference from Embodiment 1 is that the composition of the solid electrolyte in slurry B is different. In this embodiment, the solid electrolyte is PEO.
[0131] Comparative Example 1
[0132] The difference from Example 5 is that no anodizing treatment is performed.
[0133] Comparative Example 2
[0134] Compared with Example 5, the difference is that the annealing treatment under an argon atmosphere is not performed, that is, step (3) is not included.
[0135] Comparative Example 3
[0136] Compared with Example 5, the difference is that no anodizing treatment is performed, and a porous structure is prepared on the surface of the lithium metal sheet by laser etching, with the pore size controlled to be 5 μm.
[0137] Test case
[0138] The composite lithium metal anode sheets provided in the various embodiments and comparative examples of this application were assembled into solid-state batteries, and performance tests were conducted, as follows:
[0139] (1) Assembly of solid-state batteries
[0140] Solid-state battery preparation: First, the positive electrode layer is prepared: Ternary NCM811, Li6PS5Cl solid electrolyte powder, SP, and CNT are mixed in a mass percentage ratio of 70:28:1:1 in tetrahydrofuran (THF) and ethanol solvent, with a solid content of 75%, and coated on one side of aluminum foil with a single-sided areal density of 18 mg / cm³. 2 The positive electrode sheet was obtained; then, the above-mentioned positive electrode sheet, the composite lithium metal negative electrode sheet provided in each embodiment and comparative example, the stainless steel sheet, and the spring sheet were sequentially placed into the positive electrode shell, the negative electrode shell was covered, and pressure was applied to obtain a coin cell solid-state battery. The entire assembly process was carried out in a glove box, and all test batteries were tested under the same pressure (30MPa).
[0141] (2) Interface impedance test
[0142] Electrochemical impedance spectroscopy (EIS) tests were performed on the assembled coin-type solid-state batteries using an electrochemical workstation with a frequency range of 20 mHz to 100 kHz and an amplitude of 5 mV. Equivalent circuit fitting was performed on the test results to obtain the interfacial impedance value R in the mid-frequency region. i The specific test results are shown in the table below:
[0143] Table 1
[0144]
[0145]
[0146] As can be seen from the comparison of the data of Examples 1-7 and Comparative Examples 1-3, the composite lithium metal anode sheet prepared by the method of this application can significantly reduce impedance. Due to the different selection of solid electrolytes, the impedance data of Examples 8 and 9 cannot be directly compared.
[0147] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing a composite lithium metal anode sheet, characterized in that, Includes the following steps: S1. Prepare lithium-containing metal sheets and place them in an electrolyte for anodic oxidation treatment. S2, the lithium-containing metal sheet that has undergone anodizing is annealed in a non-reactive gas atmosphere; S3, the solid electrolyte and binder are homogenized to obtain a slurry, which is then coated onto one side of the lithium metal sheet after annealing, dried, and rolled to obtain the composite lithium metal anode sheet.
2. The method for preparing the composite lithium metal anode sheet according to claim 1, characterized in that, In S1, the parameters of the anodizing treatment include: an electrolysis temperature of 20–40°C, an electrolysis time of 2–10 min, and a voltage range of 0.005–3 V. And / or, the lithium-containing metal sheet includes at least one of pure lithium metal sheet or lithium-containing alloy.
3. The method for preparing the composite lithium metal anode sheet according to claim 1, characterized in that, In S1, in the anodic oxidation process, a lithium-containing metal sheet is used as the anode and a platinum electrode is used as the cathode. And / or, the electrolyte includes a lithium salt at a concentration of 0.5 mol / L to 5 mol / L; And / or, the lithium-containing alloy includes at least one of Li-B alloy, Li-Al alloy, Li-Cu alloy, Li-Zn alloy, Li-Sn alloy, and Li-In alloy.
4. The method for preparing the composite lithium metal anode sheet according to claim 1, characterized in that, In S2, the annealing treatment temperature is 100–700°C, the time is 0.5–4 h, and the heating rate is 5–10°C / min; And / or, the inert gas includes at least one of argon and nitrogen; And / or, in S3, the drying temperature is 60-80°C.
5. A composite lithium metal anode sheet, characterized in that, It is prepared by the preparation method according to any one of claims 1-4.
6. The composite lithium metal anode sheet according to claim 5, characterized in that, include, A lithium-containing metal sheet has a first surface and a second surface opposite each other in its own thickness direction, and at least one surface has a nanoporous structure; The surface components of the nanoporous structure include at least one of lithium oxide, lithium hydroxide, lithium carbonate, and lithium fluoride. A solid electrolyte layer is located on one side surface of the lithium-containing metal sheet and fills the nanoporous structure.
7. The composite lithium metal anode sheet according to claim 6, characterized in that, The average pore size of the nanoporous structure is 20–80 nm; And / or, the thickness of the lithium-containing metal sheet is 10–30 μm; And / or, the thickness of the solid electrolyte layer is 10-50 μm.
8. The composite lithium metal anode sheet according to claim 6, characterized in that, The solid electrolyte layer comprises 93% to 97% solid electrolyte and 3% to 7% binder by total mass.
9. A lithium-ion solid-state battery, characterized in that, Including the composite lithium metal anode sheet as described in any one of claims 5-8.
10. An electrical appliance, characterized in that, Including the lithium-ion solid-state battery as described in claim 9.
